2008
DOI: 10.1016/j.echo.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Detection of Increased Carotid Intima-Media Thickness and Carotid Plaque in an Office Practice Setting: Does It Affect Physician Behavior or Patient Motivation?

Abstract: Background-The aim of this multicenter study was to determine if identifying increased carotid intima-media thickness (CIMT) or carotid plaque during office-based ultrasound screening examinations could alter physicians' treatment plans and patients' motivation regarding healthrelated behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…94 A subsequent, more recent study, on the other hand, did show that CAC screening motivated the initiation of CHD preventative measures. 95 A similar effect of office-based CIMT screening on physician behavior and patient motivation was demonstrated in a recent study 96 showing that physicians were more likely to prescribe evidence-based, CHD riskreducing interventions such as aspirin and lipid-lowering therapies if increased CIMT or carotid plaque was documented. In the same study, the act of screening itself increased patients' stated motivation to make dietary changes and increase exercise.…”
Section: Does Atherosclerosis Imaging Change Care?mentioning
confidence: 80%
“…94 A subsequent, more recent study, on the other hand, did show that CAC screening motivated the initiation of CHD preventative measures. 95 A similar effect of office-based CIMT screening on physician behavior and patient motivation was demonstrated in a recent study 96 showing that physicians were more likely to prescribe evidence-based, CHD riskreducing interventions such as aspirin and lipid-lowering therapies if increased CIMT or carotid plaque was documented. In the same study, the act of screening itself increased patients' stated motivation to make dietary changes and increase exercise.…”
Section: Does Atherosclerosis Imaging Change Care?mentioning
confidence: 80%
“…After a two-step screening process, 12 articles fulfilled the inclusion criteria. 11,[14][15][16][17][18]32,[35][36][37][38][39] Using the abstract and title on the first screen, 13 disagreements concerning eligibility for a full-text review occurred between the two reviewers (kappa=0.81). For the second screen, which was based on the full-text review of 41 studies, there was one disagreement (kappa=0.94).…”
Section: Resultsmentioning
confidence: 99%
“…In the RCTs, screening for atherosclerosis did not improve CVRF, but an increased smoking cessation rate (18% vs. 6%, p=0.03) was found in a single RCT. 11 Non-randomized studies showed potential positive effects of atherosclerosis screening on "intermediate" outcomes, such as increased motivation to change lifestyle 36,37 and an increased perception of CV risk. 14,18,37,39 However, such data were based on self-report and limited by the lack of a randomized control group.…”
Section: Discussionmentioning
confidence: 99%
“…These include abbreviated scanning protocols which make the test less time-consuming, 64 semi-automated border detection programs which improve the reproducibility and speed of measuring CIMT, 64,65 as well as the use of non-sonographer clinicians who can perform this test in an office setting rather than a traditional radiology or vascular laboratory. 66,67 Abbreviated scanning protocols include circumferential carotid plaque screening of all visualized segments of both carotid arteries as an initial step. 64 If carotid plaque is detected, CIMT imaging can be considered optional, as the detection of carotid plaques may provide sufficient justification for intensifying risk reducing therapy.…”
Section: Barriers To Clinical Usementioning
confidence: 99%